Inovasi Madrasah Dalam Pemasaran Jasa Pendidikan - Nurasiah; Cut Intan Hayati (Enlightenment Publishing, 2024)
Purpose: This study is to examine how madrasah motivation in marketing education services, this research is expected to provide an in-depth analysis of how madrasah innovation in marketing education services. Method: This research uses a qualitative approach of the mini research type which is carried out such as observation of Madrasah or interviewing relevant parties such as principals and other civitas. Through this mini research study obtained. Results: Madrasah innovation towards marketing educational services can be done by building motivation among educational personnel such as principals, vice principals, administrators and even public relations are involved in it and also students. When this all happens, madrasah innovation towards marketing educational services can run better. Marketing of educational services will progress well when the services provided can satisfy consumers. Implication: Innovation in marketing is able to improve the quality of education, marketing that is brought closer to modern marketing, namely using technology, will further create good madrasah services and can convince the public of the quality of education.